Hydrogen Sulfide Induced Carbon Dioxide Activation by Metal‐Free Dual Catalysis. Issue 13 (16th February 2016) - Kumar, Manoj; Francisco, Joseph S.
Abstract: The role of metal free dual catalysis in the hydrogen sulfide (H2 S)‐induced activation of carbon dioxide (CO2 ) and subsequent decomposition of resulting monothiolcarbonic acid in the gas phase has been explored. The results suggest that substituted amines and monocarboxylic type organic or inorganic acids via dual activation mechanisms promote both activation and decomposition reactions, implying that the judicious selection of a dual catalyst is crucial to the efficient C−S bond formation via CO2 activation. Considering that our results also suggest a new mechanism for the formation of carbonyl sulfide from CO2 and H2 S, these new insights may help in better understanding the coupling between the carbon and sulfur cycles in the atmospheres of Earth and Venus. Abstract : It's a gas, gas, gas : The role of metal‐free dual catalysis in the hydrogen sulfide‐induced activation of carbon dioxide has been explored by means of quantum chemical calculations. These results suggest a new mechanism for the formation of carbonyl sulphide in the atmospheres of Earth and Venus.